Characteristics of japanese persimmon varieties cultivated in wet subtropics according to the ecological plasticity and stability parameters - T. D. Besedina; M. D. Omarov; Z. M. Omarova; M. A. Avidzba (Новые технологии, 2018)
The combination of high potential productivity and resistance to abiotic stressors is considered to be the main priority and criterion for evaluating Japanese Persimmon varieties. All varieties of Japanese persimmon grown in humid subtropics can be divided into intensive, plastic, low ecological plasticity and homeostatic ones - not responsive to environmental changes on the basis of the analysis conducted to assess the parameters of environmental plasticity and stability, depending on the conditions of a year.